Off-resonance Saturation Magnetic Resonance Imaging of Superparamagnetic Polymeric Micelles - Khemtong, Chalermchai (2009)
An off-resonance saturation (ORS) method was used for magnetic resonance imaging of superparamagnetic polymeric micelles (SPPM). SPPM was produced by encapsulating a cluster of magnetite nanoparticles (9.9±0.4 nm in diameter) in poly(ethylene glycol)-b-poly(D,L-lactide) (PEG-PLA) copolymer micelles (micelle diameter: 60±9 nm). In ORS MRI, a selective radiofrequency (RF) pulse was applied at an off-resonance position (0-50 ppm) from the bulk water signal, and the SPPM particles were visualized by the contrast on a division image constructed from two images acquired with and without pre-saturation. Here, the effects of saturation offset frequencies, saturation durations, and RF powers on ORS contrasts were investigated as these parameters are critical for optimization of ORS MRI for in vivo imaging applications. The ability to turn “ON” and “OFF” ORS contrast of SPPM solutions permits for an accurate image subtraction and a contrast enhancement to visualize SPPM probes for in vivo imaging of cancer.